Job Satisfaction and Narimo Ing Pandum Attitudes: A Mixed Method Study in Indonesia - Murwaningsih, Tri; Akbarini, Nur Rahmi; Fauziah, Muna (Jurnal Pendidikan dan Pengajaran, 2021)
Institutions can use customer satisfaction to build loyalty and success in terms of how the agency operates. This study aims to examine the effect of job satisfaction on teacher attitudes and analyze the factors of teacher job satisfaction and the philosophy of Narimo ing Pandum. This research uses a mixed research method. One hundred teachers followed this study. The data were collected by using interview and questionnaire techniques. Data analysis was carried out using simple linear regression analysis and interactive analysis (data reduction, data presentation, and levers/conclusions). The findings of this study reveal a significant effect of job satisfaction on the attitudes of teachers of SMK Narimo ing Pandum. The highest factor of teacher job satisfaction is the support of colleagues (20.27%) and the lowest factor is the work itself (13.77%). Meanwhile, the highest proportion of Narimo ing Pandum attitude is honest and sincere (22.28%) and the lowest percentage is gratitude (13.17%). This finding contributes that school principals need to give serious attention to job satisfaction and attitudes towards Narimo ing Pandum by optimizing what teachers need in teaching. It is hoped that teachers can apply the principles of Narimo ing Pandum.